2017
DOI: 10.2807/1560-7917.es.2017.22.27.30569
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance perspective on Lyme borreliosis across the European Union and European Economic Area

Abstract: Lyme borreliosis (LB) is the most prevalent tick-borne disease in Europe. Erythema migrans (EM), an early, localised skin rash, is its most common presentation. Dissemination of the bacteria can lead to more severe manifestations including skin, neurological, cardiac, musculoskeletal and ocular manifestations. Comparison of LB incidence rates in the European Union (EU)/European Economic Area (EEA) and Balkan countries are difficult in the absence of standardised surveillance and reporting procedures. We explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 36 publications
1
68
0
2
Order By: Relevance
“…In 2006 roughly 85 000 cases of Lyme borreliosis were reported annually in Europe,14 and more recently, this was estimated to be approximately 230 000 in Western Europe, although this is thought to be an underestimate 15. Incidences in some countries peak as high as 350 per 100 000 population and have increased in the past two decades 151617. Lyme borreliosis is also highly prevalent in North America; the number of reported cases has gradually increased over time in the US,18 and the Centers for Disease Control and Prevention (CDC) has estimated that there are more than 300 000 new cases each year 19.…”
Section: Incidence and Epidemiologymentioning
confidence: 99%
“…In 2006 roughly 85 000 cases of Lyme borreliosis were reported annually in Europe,14 and more recently, this was estimated to be approximately 230 000 in Western Europe, although this is thought to be an underestimate 15. Incidences in some countries peak as high as 350 per 100 000 population and have increased in the past two decades 151617. Lyme borreliosis is also highly prevalent in North America; the number of reported cases has gradually increased over time in the US,18 and the Centers for Disease Control and Prevention (CDC) has estimated that there are more than 300 000 new cases each year 19.…”
Section: Incidence and Epidemiologymentioning
confidence: 99%
“…Given that most of the binding energy is typically derived from 4-6 amino acids [17], the specificity of antigen-antibody interaction is defined by only a few anchor residues within an epitope [29, [96][97][98]. Previoulsy, we [27] and others [34] demonstrated that the four-amino-acid consensus is a minimum motif length, which is sufficient to define an antibody specificity. Thus, the high copy number of shorter targets in the initial selection makes the process of target recognition more deterministic.…”
Section: Fig 5 Clustvis-generated Principal Component Analysis Plotsmentioning
confidence: 99%
“…In our recent studies [10,31,32], we successfully applied the PDRPL/NGS to define repertoires of antibodies developed in mice and rabbits that had an active infection with Borrelia burgdorferi, the bacterial agent of Lyme disease (LD) [33][34][35][36][37][38][39][40][41]. LD pathogen has the capacity to establish persistent infection in mice, the primary natural mammalian reservoir of B. burgdorferi in the United States [42][43][44][45][46][47], and human patients [48][49][50][51][52][53], despite very strong anti-B.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, Lyme disease occurs worldwide [5]. The reasons for the increasing incidence of Lyme disease include the constantly changing geographical range of ticks and the extension of the feeding period for ticks (which are a vector of the B. burgdorferi spirochete -a biological pathogen that causes Lyme disease in humans) [6]. Migrating birds that carry infected ticks to areas where spirochetes were not previously present play an important role in disease spread [5].…”
Section: Introductionmentioning
confidence: 99%